2017
DOI: 10.3390/app7030288
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of High-Intensity Focused Ultrasound Heating by Short-Pulse Generated Cavitation

Abstract: Abstract:A target tissue can be thermally coagulated in high-intensity focused ultrasound (HIFU) treatment noninvasively. HIFU thermal treatments have been clinically applied to various solid tumors. One of the problems in HIFU treatments is a long treatment time. Acoustically driven microbubbles can accelerate the ultrasonic heating, resulting in the significant reduction of the treatment time. In this paper, a method named "trigger HIFU exposure" which employs cavitation microbubbles is introduced and its re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 81 publications
(168 reference statements)
0
16
0
Order By: Relevance
“…Our SDT system utilizes a specific HIFU irradiation sequence consisting of a trigger pulse and heating wave to generate and maintain cavitation bubbles (Yoshizawa et al, 2017), which induce a cytotoxic effect. In conventional ultrasound diagnosis, a contrast agent with a microbubble is used intravenously to obtain a clear ultrasound image.…”
Section: Discussionmentioning
confidence: 99%
“…Our SDT system utilizes a specific HIFU irradiation sequence consisting of a trigger pulse and heating wave to generate and maintain cavitation bubbles (Yoshizawa et al, 2017), which induce a cytotoxic effect. In conventional ultrasound diagnosis, a contrast agent with a microbubble is used intravenously to obtain a clear ultrasound image.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of the proposed exposure sequence has been confirmed in regard to the thermal effect of ultrasound. 9,10) Since cavitation microbubbles are so potent to induce bioeffects of ultrasound, 11) they can also damage normal tissues unless they are well localized in the tissue to be treated. Therefore, the spatiotemporal monitoring of the generated cavitation bubbles is necessary to ensure the safety as well as the effectiveness of such treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high frequencies of ultrasonic waves, oscillating air bubbles are generated, which drastically change the liquid status. Extremely rapid heating or cooling, and pressures of up to several hundred mega Pascals, are observed in transient cavities, while the bulk of the liquid remains at an ambient temperature and pressure [10,11]. In 2010, Skorb's group reported that a metal aluminum film with nanopores on parts of its surface was obtained in water using ultrasound cell disrupting equipment [12].…”
Section: Introductionmentioning
confidence: 99%
“…Effects of ultrasonication and the etching agent on the formation of nanopores on the surfaces of (a) aluminum and (b) copper foil.Kinetics of this heterogeneous reaction include the following five steps: (1) Diffusion of the chemical agent to the metal surface; (2) adsorption of the chemical agent; (3) interface chemical reaction at the metal solid surface with the chemical agent; (4) desorption; and (5) diffusion of the reaction products to the bulk solution[10][11][12]. Generally, the reaction is determined by a slow interface chemical reaction.…”
mentioning
confidence: 99%